2022
DOI: 10.1039/d2cp02165j
|View full text |Cite
|
Sign up to set email alerts
|

The structural, electronic and optical properties of four α-Se-based heterostructures with hyperbolic characteristics

Abstract: The physical properties and potential applications of two-dimensional (2D) materials can be effectively modulated and enriched by constructing van der Waals heterostructures (VDWHs) with two or more 2D monolayer materials....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…[ 41 ] Zhao et al reported that the optical absorption of the four α‐Se‐based vdWHs in the visible and ultraviolet light regions is significantly enhanced compared with the individual layers. [ 42 ] Generally, there are three different band alignments of vdWHs, which are straddling (type‐I), staggered (type‐II), and broken (type‐III). [ 43 ] In staggered band alignment vdWHs, electrons and holes are confined to different monolayers, leading to greater spatial separation than intralayer excitons, facilitating the formation of interlayer excitons and further extending their lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] Zhao et al reported that the optical absorption of the four α‐Se‐based vdWHs in the visible and ultraviolet light regions is significantly enhanced compared with the individual layers. [ 42 ] Generally, there are three different band alignments of vdWHs, which are straddling (type‐I), staggered (type‐II), and broken (type‐III). [ 43 ] In staggered band alignment vdWHs, electrons and holes are confined to different monolayers, leading to greater spatial separation than intralayer excitons, facilitating the formation of interlayer excitons and further extending their lifetimes.…”
Section: Introductionmentioning
confidence: 99%